(3CLfGS GdTYQs - (3ehghH Hf CMeO Hf eMeO Hf GdNVQ Hf GdMSf, CHh GdefUhQ GHf GdLhGdjbj,J (B540 (3g` s
(3ChdgG (B:s
(3bGd bGd di CHhGdYdGA CTed eG hVYg cMHjH Hf GhS ef CLfGS GdTYQ GdNeSI YTQ Ydi EKfi YTQ LfSkG gi s
(3BNQgG (B:s
(3aGdRGj dCHj RcQjG hGdUGO dCHf GdUbQ JeJ s
(3fSNI ecQQI ef GdejcQhajde Qbe (B78s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B123 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B53s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(6) s
Keywords: (3GdYQhV hGdbhGais